Diverse Burkholderia Species Isolated from Soils in the Southern United States with No Evidence of B. pseudomallei. - Carina M Hall (PLoS ONE, 2015)
The global distribution of the soil-dwelling bacterium Burkholderia pseudomallei, causative agent of melioidosis, is poorly understood. We used established culturing methods developed for B. pseudomallei to isolate Burkholderia species from soil collected at 18 sampling sites in three states in the southern United States (Arizona (n = 4), Florida (n = 7), and Louisiana (n = 7)). Using multi-locus sequence typing (MLST) of seven genes, we identified 35 Burkholderia isolates from these soil samples. All species belonged to the B. cepacia complex (Bcc), including B. cenocepacia, B. cepacia, B. contaminans, B. diffusa, B. metallica, B. seminalis, B. vietnamiensis and two unnamed members of the Bcc. The MLST analysis provided a high level of resolution among and within these species. Despite previous clinical cases within the U.S. involving B. pseudomallei and its close phylogenetic relatives, we did not isolate any of these taxa. The Bcc contains a number of opportunistic pathogens that cause infections in cystic fibrosis patients. Interestingly, we found that B. vietnamiensis was present in soil from all three states, suggesting it may be a common component in southern U.S. soils. Most of the Burkholderia isolates collected in this study were from Florida (30/35; 86%), which may be due to the combination of relatively moist, sandy, and acidic soils found there compared to the other two states. We also investigated one MLST gene, recA, for its ability to identify species within Burkholderia. A 365bp fragment of recA recovered nearly the same species-level identification as MLST, thus demonstrating its cost effective utility when conducting environmental surveys for Burkholderia. Although we did not find B. pseudomallei, our findings document that other diverse Burkholderia species are present in soils in the southern United States.